Periodic island-layer-island growth during deposition of ultrastable metallic glasses - Fan Yang (Nature Portfolio, 2021)
Ultrastable metallic glasses form by surface diffusion on a substrate during deposition. Here, this process is shown to involve the collective diffusion of atoms in a cyclic process, involving the formation of islands, their coalescence into a layer, followed by further island formation.